Strategi Ladokgi TNI AL R.E. Martadinata dalam Pencegahan Penularan Covid-19 Guna Mendukung Tugas TNI Angkatan Laut - Ponangsera, Iko Sarikanti; Kurniadi, Anwar; Sari, Deffi Ayu Puspito (Universitas Budi Luhur, 2023)
Dental and oral health services at Indonesian Navy Dental Institution R.E Martadinata might continue during the COVID-19 pandemic so as not to interfere with the duties of Indonesian Navy soldiers. For this reason, the implementation of dental and oral treatment might implement the procedures to prevent COVID-19 transmission. This study aimed to analyze transmission prevention procedures and strategies to prevent transmission of COVID-19. This study used a qualitative method with a descriptive design. The results showed that: 1) the procedure for preventing the transmission of COVID-19 in Indonesian Navy Dental Institution R.E Martadinata was carried out by applying strict health protocols and testing; 2) The strategy carried out is to provide initial training such as Basic Life Support, COVID-19 screening training, and PCR examinations, and increase the capacity of health workers by installing air purifiers in every room, equipping dental units with High Volume Evacuators (HVE). The conclusion in the study was that the procedure for preventing the transmission of COVID-19 and the strategy carried out by Indonesian Navy Dental Institution R.E Martadinata were good for preventing the transmission of COVID-19. Thus, dental and oral treatment services can continue to run properly without neglecting the safety of health workers and patients.